The pursuit of history : aims, methods and new directions in the study of history - Tosh, John. (2015)
"This classic introduction to the study of history invites the reader to stand back and consider some of its most fundamental questions: What is the point of studying history? How do we know about the past? Does an objective historical truth exist and can we ever access it? In answering these central questions, John Tosh argues that, despite the impression of fragmentation created by postmodernism in recent years, history is a coherent discipline which still bears the imprint of its nineteenth-century origins. Consistently clear-sighted, he provides a lively and compelling guide to a complex and sometimes controversial subject, while making his readers vividly aware of just how far our historical knowledge is conditioned by the character of the sources and the methods of the historians who work on them. The sixth edition has been substantially revised and updated throughout. New for this edition are: a brand new chapter on public history; sections on digitised sources and historical controversy; discussion of topics including transnational history and the nature of the archive; an expanded range of examples and case studies; a comprehensive companion website providing valuable supporting material, study questions and suggestions for further reading. Lucid and engaging, this edition retains all the user-friendly features that have helped to make this book a favourite with both students and lecturers, including marginal glosses, illustrations, suggested further reading and boxed guides to key events and people. Along with its companion website, this is an essential guide to the theory and practice of history"--Provided by publisher.
"Discusses historiography and the theory and practice of history. Supplemented by illustrations, marginal glosses and suggestions for further reading"--Provided by the publisher.
Historical awareness -- The uses of history -- Mapping the field -- The raw materials -- Using the sources -- Writing and interpretation -- The limits of historical knowledge -- History and social theory -- Cultural evidence and the cultural turn -- Gender history and postcolonial history -- Memory and the spoken word -- History beyond academia.
Includes bibliographical references and index.
Keywords: Historiography; History -- Philosophy; Historiography -- Philosophy; History -- Methodology; Historiography -- Methodology; Great Britain -- Historiography